Peran Guru Bimbingan dan Konseling dalam Mencegah dan Mengatasi Perilaku Menyimpang Siswa di Madrasah Aliyah An-nur Bener Meriah Aceh - Ifnaldi Ifnaldi (INTELEKTIUM, 2022)
Guidance and Counseling teachers in schools have a big role in preventing student deviant behavior, preventive efforts are carried out by counselors or counseling teachers to always anticipate various problems that may occur and try to prevent them from being experienced by students. This study aims to describe the efforts of BK teachers in preventing deviant behavior in Madrasah Aliyah An-nur Bener Meriah. The research method used is a type of qualitative research. Data collection techniques using interviews, observation and documentation. The data analysis technique used was through the stages of data reduction, data presentation and conclusion drawing. The results showed that the role of guidance and counseling teachers at MA An-nur in preventing the occurrence of deviant behavior by making preventive or preventive and curative or healing efforts.